Domenico Losurdo and contemporary critical thinking - Sousa, Francisco Pereira de (2023)
Domenico Losurdo's thinking is of immense contribution to the current global geopolitical and geoeconomic understanding: in addition to providing important conceptual tools for criticizing contemporary reality, it establishes a new perspective of interpretation for the fight against capitalist, imperialist and neocolonialist oppression exercised by the great powers in relation to the global south.